Research progress of operational transfer path analysis method - Yingying LU; Wei CHENG; Jiantao LU; Zhousuo ZHANG (Journal of Hebei University of Science and Technology, 2015)
Firstly, the basic principles, the advantages, the disadvantages and the engineering applications of the conventional TPA, OTPA, OPAX and mixed TPA in recent years are comprehensively analyzed. Meanwhile, the potential applications of power flow in the TPA field are especially discussed. Secondly, focused on the OTPA method, an acoustic transfer path system by spherical radiation transfer path simulation system and a vibration transfer path experiment system by a rectangular plate vibrator excitation are designed considering the effects of the distance from reference points. The results show that the relative error between the OTPA values and the theoretical values as well as the experimental values is less than 5% and 8% respectively. At the same time, OTPA is sensitive to noise. When the noise is lower, the nearer reference points can improve the precision of OTPA method. Therefore, it is needed to arrange sensors and design operating conditions reasonably. Finally, the development trend of TPA method is presented.